The spirit of America : a state-by-state celebration - Mathes, Charles; Hope, Bob (New York City : Gallery Books, 1990)
Text and photos provide a portrait of each state including the origin of its name, flower, state capital, bird, and famous people.
Introduction : The Northeast : The Southeast : The Midwest : The West : Credits/Index to the states.
"An M & M book"--T.p. verso.
"Prepared and produced by Moore & Moore Publishing"--T.p. verso.
Includes index.
Keywords: United States -- Description and travel -- 1981-